Additive manufacturing of TiC nanoparticles strengthened stainless steel - Hoi, Ying Xian (Nanyang Technological University, 2022)
Additive manufacturing is becoming more well used to create various product that is otherwise complicated or near-impossible to create with traditional manufacturing methods such as milling. Among all the additive manufacturing processes, selective laser melting is one of the more popular techniques with its ability to use metal powder and manufacture a product by building it layer by layer. This allows a more complicated shape to be produced while at the same time the properties of the final product can be tweaked depending on the input powder used. Stainless steel 316 is commonly used due to its high corrosion resistance, however, its low yield strength restricts this material to be used for various applications. Therefore, there has been constant studies in trying to improve the strength of stainless steel 316 through various method. This report will look into strengthening 316L through the addition of 1 wt% and 3 wt% of TiC nanoparticles. The samples will be mixed in a low-energy ball milling to ensure homogeneity. After the SLM process, the sample will undergo cutting, mounting, grinding, polishing, and etching to understand the microstructure of the samples via the optical microscope, EBSD and SEM will also be conducted. Through the addition of TiC, grain refinement was observed with 22.5% refinement for 1 wt% addition and a further 51% for 3 wt% addition. Microhardness and tensile tests are also conducted and with the addition of TiC, the microhardness increased from 219.05 HV to 258.98 HV and 280.99 HV respectively while the ultimate strength also increased from 721.571 MPa to 888.381 MPa and 987.465 MPa.